CASHLESS PAYMENT SEBAGAI INOVASI MANAJEMEN KEUANGAN PENDIDIKAN PONDOK PESANTREN - Fitria , Ulfa (Jurnal Manajemen Pendidikan Islam Darussalam, 2024)
The development of digital technology is entering the era of society 5.0 where humans have a close relationship with technology in their lives. This study aims to determine the mechanism for implementing cashless payments as an innovation in the financial management of the Darussalam Islamic boarding school Blokagung Banyuwangi Tegalsari Banyuwangi. This research uses a qualitative descriptive research method. In this research, the researcher himself is the instrument (human instrument) and there is a supporting instrument in the form of an interview guide grid. Data collection was carried out using observation, interviews and documentation techniques. The validity of the data in this research uses data triangulation. The results of this research are: The implementation of the cashless payment system at the Darussalam Islamic Boarding School Blokagung Tegalsari Banyuwangi was carried out in four stages, namely: Determining cashless payment system innovation, Determining the cashless payment system budget, Implementing the cashless payment system program, Evaluation of the implementation of the cashless payment system.